Green Synthesis of Silver Nanoparticles from Endophytic Fungus Alternaria carthami-KUMBMDBT-30 - Dadayya, Manjunatha; Subhakar, Akarsh; Gurubasajar, Nandish; Thippeswamy, Megha Gowri; Veeranna, Sowmya Hirakannavar; Basaiah, Thippeswamy (Asian Journal of Biological and Life Sciences)
In this study, an extract from the Alternaria carthami-KUMBMDBT-30 strain was used to make silver nanoparticles in a way that was both cheap and good for the environment. Among other spectroscopic tools, the Bio-spectrophotometer, FTIR, SEM-EDAX, XRD, and DLS were used to look at how Alt-AgNPs form. Fourier Transform Infrared Spectroscopy (FTIR) analysis showed that there were peaks at 3739°, 3260°, 2903°, 2845°, 2067°, 1620°, 1524°, 1219°, and 1025° cm-1 that were related to different functional groups. SEM (Scanning Electron Microscopy) analysis showed that Alt-AgNPs (Alternaria carthami- synthesized silver nanoparticles) formed in a shape that was almost spherical and uniform. Energy Dispersive Analysis of X-ray (EDAX) was used to figure out what the Alt-AgNPs were made of. X-ray Diffraction (XRD) analysis at 2Ø degree values can be linked to the (111), (200), (220), (311), and (222). The distributed Alt-AgNPs sizes were measured with Dynamic Light Scattering (DLS), which showed that they were 97.15 nm in size. The studies results show that Alt-AgNPs might be useful in biomedical applications.
Keywords: Alt-AgNPs.; Alternaria carthami; Endophytic fungus